PHYSIOTHERAPY AFTER SURGICALLY STABILIZED PROXIMAL TIBIA FRACTURE - R. Tasheva (Trakia Journal of Sciences)
THE AIM OF THIS STUDY is to present the physiotherapy for overcoming the substitution movements and to restore the correct function in the phase of relative protection after surgical stabilized proximal tibia fracture. MATERIAL AND METHOD Seven patients after fracture in the proximal lateral compartment of the tibia (type b1 in AO classification) with an average age of 42, 9 years were treated. After surgery, an average of 30 days of the brace was used for relative protection. The aim of the physiotherapy was to overcome muscle imbalance to achieve proper movement in the respective planes. Emphasis on recovery was the proper weight bearing on the operated lower limb. RESULTS The results of the first recovery phase demonstrated very limited knee flexion in range of 22, 7º, and knee extension deficit in the range of -15º. After two weeks the results progressed to 115, 5º flexion and full restoration of the extension. Control of edema and hypotrophy of the thigh were proven by circumference. CONCLUSION The adequate physiotherapy provides overcoming of the substitution movements and to restore the correct knee function in the phase of relative protection after surgical stabilized fracture in the proximal tibia.